Evaluation of Condensation Friction Pressure Loss Refrigerant 134-a in Internal Horizontal Tube Condenser by CFD - Bambang Harjanto; Teguh Hady Ariwibowo; Fifi Hesty Sholihah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Energy crisis stimulates some efforts to empower low heat source. Organic Rankine Cycle is wise way that absorbs low heat gain easily. A device is horizontal condenser where two phase flow of R134a is happening in. Two phase flow is difficult to be solved due to its complexity. An annular flow regime dominates which is plotted as main assumption. It has plotted in Thome Flow Regime Map as variations of mass flux in similar vapor fraction. In CFD solver, flow is analyzed as pseudo, vapor and liquid mixed well, as consequence it will be single phase. It will be solved by SST method as viscous model that needs a multiplier numerical solver to transform from single phase into two phases. A multiplier depends on vapor fraction which is dominated of interfacial shear stress phenomenon as turbulent flow. Muller Steinhagen and Heck’s method is implemented due to its accuration. The value result of pressure loss correlates proportionally to mass flux. In similar mass flux, pressure loss increases as increasing linearly of vapor fraction due to high value of void fraction. The accuracy is within 91 %.